The Representation of Mount Slamet Disaster in The Online Media of Tempo and Time - Fadhlillah Sariwibawa Ahmad Zaeni (Universitas Pendidikan Indonesia (UPI), 2016)
The present study examines the representation of Mount Slamet disaster in online media in two news practitioners, namely Tempo and Time. This study mainly employs a descriptive qualitative method. The data include twelve articles taken from Tempo and one article from Time related to Mount Slamet’s volcanic activity. The analysis employs the framework developed by van Dijk (2009), i.e. the socio-cognitive approach (SCA), which includes macrostructure and microstructure analyses. Halliday’s transitivity (Halliday Matthiessen, 2014) is used in microstructure analysis to examine the representation of experiences presented in the articles. The macrostructure analysis discloses three findings. These include the issues discussed in relation to the Mount Slamet disaster, the writing strategy of quotation, and the use of sources. Both Tempo and Time have a similarity of quotation strategy despite having differences in terms of variation of topics and the sources used in the articles. In microstructure analysis, the study reveals that both Tempo and Time represented the volcanic disaster mostly in material and verbal processes. The similar strategy of representation employed by the two media seems to be affected by the nature of the genre and the experience being represented. However, there is a wide difference in the number of reports made by the two media. This appears to result from different levels of concern: Tempo, as a local media, expresses more concern by writing many more reports than Time, an international media.Keywords: Socio-cognitive Approach, Representation, Mount Slamet Disaster, Online Media